A contribution to the knowledge of Namibian Atherigona Rondani (Diptera: Muscidae), with the descriptions of four new species and two new subspecies - Deeming, John C.; Kirk-Spriggs, Ashley H. (Zootaxa, 2024)
This paper provides an account of all species of Atherigona Rondani known from Namibia, all of which are known from males. The study is based largely on material deposited in the National Museum of Namibia, Windhoek, supplemented by some material deposited in other museums. Fifty-three taxa are listed in total, 14 of which were previously recorded from the country and 33 representing new country records for Namibia. Four species are described and figured as new to science and a further two as subspecies. The new species are: A. (s. str.) australis Deeming, sp. nov., A. (s. str.) maraisi Deeming, sp. nov., A. (s. str.) mulleri Deeming, sp. nov. and A. (Acritochaeta) tsumeb Deeming, sp. nov. and the new subspecies: A. (s. str.) robertsi okavango Deeming, ssp. nov. and A. (Acritochaeta) yorki namibiensis Deeming, ssp. nov. Character states differentiating A. (Ac.) tsumeb, sp. nov. from its closest congener, A. (Ac.) gracilipalpis Deeming, 1971, are presented in a tabulated form and an identification key is provided to separate Afrotropical species with pale yellow vibrissae. The previously undescribed female tergite 8 is figured for the first time for four species, viz., A. (s. str.) angulata Deeming; A. (s. str.) corrugata Deeming; A. (s. str.) parvihumilata Muller; and A. (s. str.) pulla (Wiedemann). Additional new country records are indicated with voucher specimens as follows: A. (s. str.) falcata (Thomson): Bhutan and Thailand; A. (s. str.) humeralis (Wiedemann): Botswana; A. (s. str.) nigrapicalis Deeming: Senegal; A. (s. str.) occidentalis Deeming: Zambia; A. (s. str.) pulla (Wiedemann): Burkina Faso, Chad, Gambia, Ethiopia, Israel and Tunisia; A. (s. str.) tomentigera Emden: Zambia; and A. (Acritochaeta) yorki ssp. yorki Deeming: Benin, Côte d’Ivoire, Ethiopia and Ghana. Cereal crop production in Namibia is briefly discussed and a table provided of potential or suspected pest species associated (in the larval stages) with Namibia’s main cereal crops.